(3habG dbGfhf GdJLGQI GdLOjO Qbe (B1999s - (3eUWai ceGd(B, (3Wgs ((3GdGScfOQjI(B:s (3OGQ GdeWHhYGJ GdLGeYjI(B,s, 2002)
(3GdYbhO GdJLGQjI(B- (3GdHjY GdJLGQj(B- (3GdQgf GdJLGQj(B- (3GdEjOGY aj GdeSJhOYGJ GdYGeI(B- (3GdhcGdI GdJLGQjI(B- (3GdSeSQI(B- (3Gdfbd(B- (3YbO fbd GdJcfhdhLjG(B-(3YedjGJ GdHfhc(B- (3GdMSGHGJ GdeUQajI(B- (3GdhOGFY GdfbOjI(B- (3GdEYJeGOGJ GdeUQajI(B- (3GdYedjGJ Ydi GdUchc GdeJOGhdI(B- (3SQjI GdMSGHGJ HGdHfhcs
Keywords: (3GdHfhcs; (3GdTjcGJs; (3GdYbhO JLGQjIs